TMPRSS2:ERG gene fusion variants induce TGF-β signaling and epithelial to mesenchymal transition in human prostate cancer cells - Ratz, Leonie; Laible, Mark; Kacprzyk, Łukasz Antoni; Wittig-Blaich, Stephanie Maritta; Tolstov, Yanis; Duensing, Stefan; Altevogt, Peter; Klauck, Sabine; Sültmann, Holger (OncoTarget, 2017)
TMPRSS2:ERG (T/E) gene fusions are present in approximately 50% of all prostate cancer (PCa) cases. The expression of fusion mRNAs from distinct T/E variants is associated with clinicopathological parameters, while the underlying molecular processes remain unclear. We characterized the molecular mechanisms and functional implications caused by doxycycline (Dox)-inducible overexpression of the frequent T/E III and VI fusion variants in LNCaP cells. Induction of T/E expression resulted in increased cellular migratory and invasive potential, and reduced proliferation and accumulation in G1 phase. T/E overexpressing cells showed epithelial-to-mesenchymal transition (EMT), as demonstrated by upregulation of TGF-β and WNT pathway genes, mesenchymal markers, and increased phosphorylation of the p38 MAPK. Augmented secretion of TGF-β1 and -β2, and T/E-mediated regulation of ALK1, a member of the TGF-β receptor family, was detected. ALK1 inhibition in T/E overexpressing cells blocked p38 phosphorylation and reduced the expression of the TGF-β target genes VIM, MMP1, CDH2, and SNAI2. We found a T/E variant VI-specific induction of miR-503 associated with reduced expression of SMAD7 and CDH1. Overexpression of miR-503 led to increased levels of VIM and MMP1. Our findings indicate that TGF-β signaling is a major determinant of EMT in T/E overexpressing LNCaP cells. We provide evidence that T/E VI-specific transcriptional modulation by miR-503 accounts for differences in the activation of EMT pathway genes, promoting the aggressive phenotype of tumors expressing T/E variant VI. We suggest that ALK1-mediated TGF-β signaling is a novel oncogenic mechanism in T/E positive PCa.